Peran Kelompok Rujukan dalam Meningkatkan Popularitas Mubaligh - Uwes Fatoni; Asep Mugni (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2018)
This research is studying about how a reference group can increase a popularity of Dr. K.H. Abdul Hamid as a Mubaligh. This research uses a qulaitiative method. Informan in this study were Abdul Hamid himself, some a member of majelis ta’lim which is often listen to da’wah of Abdul Hamid, and His friends who often accompany Abdul Hamid in his da’wah activities. Primary qualitative data retrieved directly using indepth interviews to obtain data. The purpose of this study is how the reference group capable to develop a popularity of Abdul Hamid. The theory uses a group theory by Lazasfeld, Berelson, and Gaudet. Conculation of this research are the reference group proven effective in develop a popularity of person. If it’s positiv will be positive. And if it’s negative will be negative too.